Nasal Polyposis: An Overview of Etiology, Diagnosis, and Modern Treatment Options - Dudvarski, Zoran; Nesic, Vladimir; Jakoviljevic, Sasa; Radivojevic, Nemanja; Jovanovic, Katarina (Medical Research, 2026)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a chronic, heterogeneous inflammatory disease associated with substantial impairment of nasal breathing, olfaction, and patients’ quality of life. Its etiology and pathogenesis are multifactorial and involve epithelial barrier dysfunction, impaired mucociliary clearance, dysbiosis, biofilm formation, Staphylococcus aureus, eosinophilic/type 2 inflammation, local IgE production, tissue remodeling, environmental factors, and numerous comorbidities. The coexistence of asthma and intolerance to aspirin and/or nonsteroidal anti-inflammatory drugs is particularly important within the unified airway concept. Diagnosis is established by correlating characteristic symptoms with objective findings obtained by clinical and/or endoscopic examination of the nose and computed tomography of the paranasal sinuses. Assessment of disease severity, comorbidities, and relevant differential diagnoses is essential. The cornerstone of treatment is intranasal corticosteroid therapy and nasal saline irrigation, whereas systemic corticosteroids, endoscopic sinus surgery, and biologic therapy are reserved for more severe, recurrent, or uncontrolled disease. The diagnostic and therapeutic approach to CRSwNP requires differentiation between disease phenotypes and endotypes, recognition of type 2 inflammation, active management of associated conditions, and continuous monitoring of treatment response based on symptoms, endoscopic findings, quality of life, and the need for additional interventions. This review summarizes current evidence on the etiology, pathogenesis, clinical presentation, quality of life, diagnostic criteria, and modern treatment options for CRSwNP, based on systematic reviews, clinical guidelines, and original studies. An individualized approach, adequate control of local disease and comorbidities, and regular follow-up are key to improving long-term treatment outcomes.
Keywords: chronic rhinosinusitis with nasal polyps, type 2 inflammation, nasal endoscopy, endoscopic sinus surgery, biologic therapy